Diversity Scaling of Human Digestive Tract (DT) Microbiomes: The Intra-DT and Inter-individual Patterns - Chen, Hongju (Daisy); Yi, Bin; Liu, Qiang; Xu, Xia; Dai, Lin; Ma, Zhanshan (Sam) (Frontiers in Genetics, 2021)
The human gut microbiome has been extensively studied, but its diversity scaling (changes) along the DT (digestive tract) as well as their inter-individual heterogeneities have not been adequately addressed in our opinion. Here we fill the gap by applying the diversity-area relationship (DAR), a recent extension to the classic species-area relationship (SAR) in biogeography, by reanalyzing the dataset of over 2000 16s-rRNA microbiome samples obtained from 10 DT sites of over 200 individuals. We sketched out the biogeography “maps” for each of the 10 DT sites by cross-individual DAR analysis, and the intra-DT distribution pattern by cross-DT site DAR analysis. Regarding the inter-individual biogeography, it was found that all DT sites have the invariant scaling parameter—all sites possessing the same diversity change rate across individuals, but most sites have different potential diversities. In terms of the genus richness, an average individual hosts approximately 20% of the population-level genus richness (total bacterial genus of a human population). In contrast, in terms of community biodiversity, the percentages of individual vs. population may exceed 90%. This suggests that the differences between individuals in their DT microbiomes are predominantly in the composition of bacterial species, rather than how their abundances are distributed (i.e., biodiversity). Regarding the intra-DT patterns, the scaling parameter is larger—suggesting that the intra-DT biodiversity changes are more dramatic than inter-individual changes. On average, each site contains 21%-36% of genus diversity of the whole DT, and the percentages are even higher at the higher taxon levels.